Effect of active oxygen gel on the clinical parameters of MRONJ - Bruna Cristina de Cristo; Hassan Yousef Saleh; Suyany Weiss; Aline Sebastiani; Mohammed Elsalanty; Rafaela Scariot; Tatiana Miranda Deliberador (Saudi Dental Journal)
Purpose: The aim of this work was to evaluate the effectiveness of a gel with active oxygen in the prevention of MRONJ. Methods: Using split-mouth study design, twelve Wistar rats were used, females (n = 6) and males (n = 6). All rats received a weekly intravenous injection of zoledronate (80 μg / kg body weight in PBS) for 8 weeks. Then, the animals underwent surgery to remove the first and second right and left mandibular molars to induce osteonecrosis. The animals received topical application of oxygen gel (blue®m) on the right-side extraction site (Group T) 3 times a week until euthanasia after 6 weeks, with no intervention on the left side (Group C). The clinical parameters analyzed included the presence and dimension of bone exposure, suppuration and epithelialization. Results: Statistical analysis using chi-square and Mann-Whitney test (p value < 0.05) demonstrated that group C had more severe signs of MRONJ at euthanasia than in the group T. Conclusion: Within the limitations of this pilot study, we can conclude that the application of active oxygen gel could be beneficial in the prevention of MRONJ.